(untitled) (American Journal of Islam and Society, 2013)
To label Adam Hanieh’s Capitalism and Class in the Gulf Arab States an afterstudy of the 2008 financial crisis is a grossly unfair assessment. While the book does explore the implications of the Gulf states’ financial slump, it also provides a nuanced analysis of their class structures and relation to the global capital system. The exponential growth of the Gulf Cooperation Council (GCC) states is the book’s main subject; however, Hanieh dexterously avoids the common errors involved in the region’s economic analysis and thus adds to the corpus of literature pertaining to both the GCC and the wider global economy. The class structures and wealth prevailing in the GCC are often seen as an outcome of the states being oil rich. Hanieh problematizes this narrative by positing that this wealth and structuring is not “accidental” and that while oil is undeniably important, it is not the sole reason for the region’s situation. He urges the reader to look beyond the hydrocarbon wealth, because “much like its desert cousin, the mirage – what visitors actually see in the oil-fueled boom is not the full picture” (p. 2). Hanieh’s choice of viewing the GCC holistically, instead of addressing specific nation-states, is significant. The “internationalization” of the local economy and class structure results in the dissolution of class boundaries among the states and paves the way for capitalism. But at the same time, however, capitalism needs to be valorized in a coherent and material time and space. This valorization has taken the special form of the regional GCC and becomes the study’s focal point. This regionalization has displaced “power upwards to the regional scale, weakening the ability of the individual member states to control the movement of goods and capital within the intra-GCC space” (p. 104). The author also problematizes the “rentier-state” theory through a Marxian framework. He urges the reader not to consider the state, and particularly the states of the Gulf nations, as a “thing” or an automatic reflection of the capitalist class, but rather as “a particular expression of class formation” (p. 12). This also implies that the state has greatly facilitated the development of the GCC’s prevailing “hot-house” economy (p. 15). The study’s regional nature culminates in the analysis of “Khaliji” capital. In the Gulf states, the internationalization of capital manifests itself in a regional form as the “circuits of capital are themselves elaborated at the ...